The relationship of knowledge and attitude of pregnant women about early rupter of room (opm) in Palmarum Clinic Pamatang Raya - Yunardi; Yeci Theresia Simanjuntak; Christian Rayando Butar-Butar (Institute of Computer Science (IOCS), 2022)
Premature rupture of membranes is the state of rupture of the amniotic membranes before the time of delivery. If premature rupture of membranes occurs before 37 weeks of gestation it is called premature rupture of membranes in preterm pregnancy. Under normal circumstances 8-10% of pregnant women at term will experience premature rupture of membranes (Prawirohardjo, 2009). This study aims to determine the relationship between the knowledge and attitudes of pregnant women regarding premature rupture of membranes at the Palmarum Pamatang Raya clinic in 2016. The research method was descriptive analytic. The sample in this study was the entire population (total sampling) of 35 people. From the results of this study it was found that the majority of pregnant women aged <20 years as many as 12 people (34.3%) had poor knowledge about premature rupture of membranes, namely as many as 9 people (25.7%). The results of the chi-square test obtained p = 0.041 and the majority of pregnant women aged 20-35 years as many as 12 people (34.3%) had an unfavorable attitude regarding premature rupture of membranes, namely as many as 8 people (22.9%). The results of the chi-square test obtained p 0.105. 11 people (31.4%) had poor knowledge about premature rupture of membranes, namely 8 people (22.9%). The results of the chi-square test obtained p = 0.000 and the majority of pregnant women with high school education as many as 11 people (31.4%) had an unfavorable attitude about premature rupture of membranes, namely 6 people (17.1%). The results of the chi-square test obtained p = 0.000. From the results of the study, the majority of pregnant women had poor knowledge of 21 people (60.0%), where there were unfavorable attitudes about premature rupture of membranes, namely 12 people (34.3%). The chi-square test results obtained p 0.000. Based on the results of the research that has been done, it can be concluded that age and education significantly influence the knowledge and attitudes of pregnant women about premature rupture of membranes. Knowledge can even influence pregnant women's attitudes about premature rupture of membranes according to the chi-square results obtained p = <0.05